The effect of Korean pop music videos on female adolescents' self-appraisal of physical attractiveness - Girado, Karen Audrey B. (2018)
This study examined the effect of Korean pop music videos by girl groups to the self-appraisal of physical attractiveness of female adolescents. Music videos can be used as tools to target women and make them think about how they should look like, given that music videos can now also be used as tools to shape the ideologies of the viewers. Hence, this examines what effects these music videos have to the ideologies of female adolescents in terms of beauty, and physical attractiveness. The series of statistical tests that were conducted throughout this study showed that the female adolescents? viewing of Korean pop music videos did affect their internal dialogues regarding physical appearance, and did not affect related emotions and schemes. In line with this, only the subjects? body mass index (BMI) and their self-esteem are the only two variables that affected how these female adolescents think about their own physical appearance. Also, the subjects? self-regulatory behaviors are predicted by their age., body mass index (BMI), self-esteem, ear level, annual family income, internalization of beauty, ideal physical appearance, importance of beauty, concern for their physical appearance, and their perceived body shape. In general, this contributes to the knowledge and theory-building in studies that tackle about new media, as well as women studies.